2018
DOI: 10.1002/cmdc.201800033
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Biological Evaluation of Indole‐2‐carbohydrazide Derivatives as Anticancer Agents with Anti‐angiogenic and Antiproliferative Activities

Abstract: A novel series of indole-2-carbohydrazide derivatives were synthesized, characterized, and evaluated for their antiproliferative activities against two cancer cell lines, HCT116 and SW480, and a normal human fetal lung fibroblast cell line, MRC-5. Among this series, compound 24 f displayed potent cytotoxic activities in vitro against HCT116 and SW480 cell lines with GI values of 8.1 and 7.9 μm, respectively, and was inactive against MRC-5 cells. The newly synthesized compounds were also evaluated for anti-angi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
1
8
0
Order By: Relevance
“…Although ZJQ-24 significantly downregulated the levels of p-VEGFR2 in HUVEC cells, the activity of VEGFR2 kinase was not prominent 23 . To clarify the functional role of ZJQ-24 in the antiangiogenic effect, we procceded to examine the interaction of ZJQ-24 with mTOR (PDB ID: 4JT6) and AKT(PDB ID: 3O96) proteins.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Although ZJQ-24 significantly downregulated the levels of p-VEGFR2 in HUVEC cells, the activity of VEGFR2 kinase was not prominent 23 . To clarify the functional role of ZJQ-24 in the antiangiogenic effect, we procceded to examine the interaction of ZJQ-24 with mTOR (PDB ID: 4JT6) and AKT(PDB ID: 3O96) proteins.…”
Section: Resultsmentioning
confidence: 85%
“…ZJQ-24 compound was identified and provided by the Key Laboratory of Medicinal Chemistry for Natural Resource (Yunnan University) 23 . The compound was prepared as 100 mM stock solutions in DMSO and aliquots stored at −20 °C, protected from light.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently,6-substituted benzoxazole or benzimidazole derivatives have been developed as multi-kinasei nhibitors, including tyrosine and serine/threonine kinases. [36] In the quest to find better anti-angiogenic agents, and as ac ontinuation of our previous studies on anticancer drug discovery, [66][67][68][69][70][71][72][73] we designed af amily of compoundsc ontaining 6-arylurea-2-arylbenzoxazoles and 6-arylurea-2-arylbenzimidazoles, with the goal of findingn ew potent anticancer agents ( Figure 2). [65] The X-ray crystallographic elucidation of the complex between 1 and VEGFR-2 demonstrated that the 2-fluoro-5-(trifluoromethyl)phenyl moiety is buried in the hydrophobic pocket, and the benzimidazole ring occupies the adenine pocket, interacting with the Cys919 residue, while the central arylurea linker is bent towardt he "hinge" region of the receptor.T herefore, we speculated that the length of the urea linker can be shortened appropriatelyt ob etter match the active site ( Figure 2).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally,2 -arylbenzoxazole analogues exhibit av arietyo fb iological activities, especially antitumora ctivities, for example, compound CJM-126. [36] In the quest to find better anti-angiogenic agents, and as ac ontinuation of our previous studies on anticancer drug discovery, [66][67][68][69][70][71][72][73] we designed af amily of compoundsc ontaining 6-arylurea-2-arylbenzoxazoles and 6-arylurea-2-arylbenzimidazoles, with the goal of findingn ew potent anticancer agents ( Figure 2). Allthe synthesized compounds were evaluated in vitro for inhibition of H1975, A549, and HeLa cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%